The role of big data analytics in measuring and analyzing the quality costs of economic units : applied research in the Iraqi company for seed production (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research aims to explain the role of huge data analyzes in measuring quality costs in the Iraqi company for the production of seed, and the research problem was diagnosed with the weakness of the approved method to measure quality costs, and the weak traditional systems of data analyzes, the researcher in the theoretical aspect relied on collecting sources and previous studies, as well as Adoption of the applied analytical approach in the practical aspect, as a set of financial analyzes were applied within the measurement of quality costs and a statement of the role of data analyzes in the practical side, the research concluded to a set of conclusions, the most important of which are: the Iraqi company to produce seeds and those working in it lacks the main elements of quality costs and how to specify them And measuring it and disclosing it with separate and limited reports that it provides, which led to the lack of recognition of the movement of these costs, their development and control over them in terms of rise or decline from one period to another, and economic units achieve many advantages as a result of data analyzes, including providing appropriate information that helps in rationalizing decisions Within the economic unit, the determination of performance in the past, and a source of future information that affects decisions.